“Make Our Languages Visible”: Lived Practice, Theory, and the Way Forward - Mingyue Michelle, G.U . (University of Jaffna, 2025)
In an increasingly interconnected world, language and identity play pivotal roles in shaping the experiences of individuals navigating diverse cultural and educational landscapes. This speech examines how the linguistic practices and identities of ethnic minority groups, as well as other marginalised communities, such as migrants and transnational individuals studying or working in new settings, are shaped. These groups navigate challenges such as language tensions between heritage and local languages, cultural identities at risk of being diminished, and institutional constraints that may limit their professional roles. However, they also capitalise on their multilingualism as embodied cultural capital and legitimise their identities in diverse ways. By connecting macro-level ideologies to micro-level identity practices, the research provides a scaffold for reimagining inclusivity in education and policy through a linguistically just lens. By highlighting these experiences, my work informs policy discussions on linguistic inclusivity, advocating for greater institutional support and critical reflection among communities.